Rasowa interpretacja dziejów Alfreda Rosenberga - Wielomski, Adam (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
One of principal aims of Alfred Rosenberg’s theory of political myth was the creation of a racial interpretation of history. It was a very important issue for National Socialism, as the movement presented itself as leading force opposing Marxism and Leninism. The great strength of communist propaganda lies in its overarching teleological vision of the world, especially Marx’s singular interpretation of the aim of history as great process of human emancipation from class society to communism, which is seen as the end point of history. It was Rosenberg’s understanding that National Socialism, as the great adversary of Marxism, must produce an alternative vision of the sense and goals of history. Rosenberg himself authored one such alternative vision. His meaning of history is a great discourse of the chronology of races struggles. It’s a perpetual war between the Nordic and Semitic races, which encompassed the fabled fall of Atlantis, Antiquity, birth of Christianity, the Middle Ages, the Reformation, the French Revolution, and the beginning of the final war between Marxism and Nazism. This article is an attempt at presenting this vision, with a brief analysis and evaluation of his scientific value.
Keywords: Rosenberg, Alfred (1893–1946); narodowy socjalizm; historia; rasy ludzkie; marksizm